Permeability Transition Pore-dependent and PARP-mediated Depletion of Neuronal Pyridine Nucleotides During Anoxia and Glucose Deprivation - Kahraman, Sibel (J Bioenerg Biomembr, 2014)
Exposure of rat cortical neurons to combined oxygen and glucose deprivation results in loss of NAD(P)H autofluorescence that is only partially reversible following restoration of oxygen and glucose, suggesting catabolism of pyridine nucleotides. This study tested the hypothesis that metabolic inhibition caused by cyanide-induced chemical anoxia plus glucose deprivation promotes both release of mitochondrial NAD(H) in response to opening of the permeability transition pore (PTP) and NAD(P)(H) degradation through activation of poly(ADP-ribose) polymerase (PARP). The NAD(P)H autofluorescence of rat neonatal cortical neurons was monitored during and following acute (10 – 30 min) exposure to the respiratory inhibitor, cyanide, in the absence and presence of glucose. Because nitric oxide-derived peroxynitrite is a known activator of PARP, we additionally assessed the effect of a nitric oxide generating agent on the NAD(P)H autofluorescence response to chemical anoxia plus glucose deprivation. Cyanide induced a rapid increase in autofluorescence, followed by a steady decline promoted by the presence of nitric oxide. This decline was primarily due to NAD(H) catabolism, as verified by measurements of total NAD(H) present in cellular extracts. Catabolism was partially blocked by an inhibitor of PARP, by a PTP inhibitor, and by either glucose or pyruvate as a source of reducing power. Overall, data suggest that metabolic, oxidative, and nitrosative stress during in vitro neuronal anoxia and glucose deprivation result in release of mitochondrial pyridine nucleotides in response to PTP opening and rapid, extensive NAD(H) degradation mediated by PARP activation. These events may contribute to the metabolic dysfunction that occurs in vivo during cerebral ischemia and reperfusion and therefore represent prime targets for neuroprotection.